Increased network centrality of the anterior insula in early abstinence from alcohol. (31st August 2021) - Bordier, Cecile; Weil, Georg; Bach, Patrick; Scuppa, Giulia; Nicolini, Carlo; Forcellini, Giulia; Pérez‐Ramirez, Ursula; Moratal, David; Canals, Santiago; Hoffmann, Sabine; Hermann, Derik; Vollstädt‐Klein, Sabine; et al.
Abstract: Abnormal resting‐state functional connectivity, as measured by functional magnetic resonance imaging (MRI), has been reported in alcohol use disorders (AUD), but findings are so far inconsistent. Here, we exploited recent developments in graph‐theoretical analyses, enabling improved resolution and fine‐grained representation of brain networks, to investigate functional connectivity in 35 recently detoxified alcohol dependent patients versus 34 healthy controls. Specifically, we focused on the modular organization, that is, the presence of tightly connected substructures within a network, and on the identification of brain regions responsible for network integration using an unbiased approach based on a large‐scale network composed of more than 600 a priori defined nodes. We found significant reductions in global connectivity and region‐specific disruption in the network topology in patients compared with controls. Specifically, the basal brain and the insular–supramarginal cortices, which form tightly coupled modules in healthy subjects, were fragmented in patients. Further, patients showed a strong increase in the centrality of the anterior insula, which exhibited stronger connectivity to distal cortical regions and weaker connectivity to the posterior insula. Anterior insula centrality, a measure of the integrative role of a region, was significantly associated with increased risk of relapse. Exploratory analysis suggests partial recovery of modular structure and insular connectivity in patients after 2 weeks. These findings support the hypothesis that, at least during the early stages of abstinence, the anterior insula may drive exaggerated integration of interoceptive states in AUD patients with possible consequences for decision making and emotional states and that functional connectivity is dynamically changing during treatment. Abstract : Network analysis of brain functional connectivity in AUD patients indicates that the anterior insula plays an exaggerated integrative role during early abstinence. Prolonged abstinence and treatment partially normalize connectivity of the insula.